2000
DOI: 10.1093/pcp/41.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Factor Involved in Flower Formation of Lemna is an  -Ketol Derivative of Linolenic Acid

Abstract: A stress-induced substance(s) (factor C) incubated with norepinephrine (NE) has strong flower-inducing activity in Lemna paucicostata. We isolated an essential component (FIF) of factor C, and clarified its chemical structure as 9-hydroxy-10-oxo-12(Z),15(Z)-octadecadienoic acid, an alpha-ketol derivative of linolenic acid, which is formed via 9-hydroperoxy linolenic acid. Synthesized FIF showed flower-inducing activity after incubation with NE (factor C activity) equivalent to that formed in the stressed Lemna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 9 publications
2
63
0
Order By: Relevance
“…Support for this hypothesis comes from two recent studies. One study provided evidence that 9-hydroxy-10-oxo-12,15-octadecadienoic acid, the ␣-ketol produced by the action of LeAOS3 on 9-HPOT, functions as a signal for flower development in Lemna paucicostata (48). Another study showed that transgenic potato plants depleted in the expression of a 9-LOX gene exhibited abnormal tuber development (49).…”
Section: Table II Substrate Specificity Of Recombinant Leaos3mentioning
confidence: 99%
“…Support for this hypothesis comes from two recent studies. One study provided evidence that 9-hydroxy-10-oxo-12,15-octadecadienoic acid, the ␣-ketol produced by the action of LeAOS3 on 9-HPOT, functions as a signal for flower development in Lemna paucicostata (48). Another study showed that transgenic potato plants depleted in the expression of a 9-LOX gene exhibited abnormal tuber development (49).…”
Section: Table II Substrate Specificity Of Recombinant Leaos3mentioning
confidence: 99%
“…2002). The total structure of KODA, including the a-ketol, carboxylic acid and two cis-olefin moieties, is strictly required for flower-inducing activity in Lemna (Yokoyama et al 2000). In this report, we showed that two other reactants of KODA and norepinephrine, which also exhibit flower-inducing activity, retain the essential structure of KODA.…”
Section: Discussionmentioning
confidence: 62%
“…KODA was prepared using lipoxygenase from rice germ and allene oxide synthase from flax seed (Yokoyama et al 2000). In order to obtain the reactants, KODA (6.45 mmol) in distilled water (3.3 L) was added to NE (6.45 mmol in 645 mL of water) in 1 M Tris-HCl buffer (pH 8.0, 320 mL) and the solution was incubated for 160 hr at 25°C.…”
Section: Analyses Of Fn7 and Fn10mentioning
confidence: 99%
“…Endogenous levels of KODA are elevated during the latter half of flower-inductive darkness, and floral induction can be canceled by the night-break treatment, that is a light exposure during the 8th hour of inductive darkness (Suzuki et al 2003). KODA was originally isolated from Lemna paucicostata during experiments related to flowering and it showed flower-inducing activity when applied exogenously (Yamaguchi et al 2001;Yokoyama et al 2000). However, exogenous application of KODA to P. nil seedlings under long day non-inductive conditions showed no effects on flowering.…”
mentioning
confidence: 99%